∫ 1 ∞ x 6 + 2 x 3 + 9 x 2 + 1 2 x 3 − 1 d x
If the integral above equals to B A cot − 1 ( D C ) for positive integers A , B , C , D such that g cd ( A , B ) = g cd ( C , D ) = 1 , evaluate 2 ( A + B + C + D ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Careful there, you need to write those d x 's. Nice work though!
A very interesting definite integral. Congratulation!
Problem Loading...
Note Loading...
Set Loading...
Given integral = ∫ 1 ∞ ( x 3 + 1 ) 2 + 9 x 2 2 x 3 − 1 d x
⇒ ∫ 1 ∞ x 2 ( ( x 2 + x 1 ) 2 + 9 ) 2 x 3 − 1 d x
⇒ ∫ 1 ∞ ( x 2 + x 1 ) 2 + 9 2 x − x 2 1 d x
Substituting x 2 + x 1 = t ⇒ d x = ( 2 x − x 2 1 ) d t we get,
3 1 tan − 1 ( 3 x 2 + x 1 ) ∣ 1 ∞ ⇒ 3 1 ( 2 π − tan − 1 ( 3 2 ) ) ⇒ 3 1 cot − 1 ( 3 2 ) ( ∵ tan − 1 ( x ) + cot − 1 ( x ) = 2 π ) ⇒ A = 1 ; B = 3 ; C = 2 ; D = 3 . ⇒ 2 ( A + B + C + D ) = 1 8